STUDI KANDUNGAN KITOSAN PADA KEONG BAKAU (Telescopium sp) DI KAWASAN KONSERVASI MANGROVE KELURAHAN PAMUSIAN KOTA TARAKAN - ., Hendrawan; Rachmawani, Dori (Jurnal Harpodon Borneo, 2011)
The purpose of this research is to know the chitosan content on telescope snail  (Telescopium sp) in mangrove conservation area of Tarakan city. Sample was determined and been measured in the location (in situ), and the chitosan content test was done in Water Quality Laboratory of Marine and fisheries faculty of Borneo Tarakan University. The result was conducted in mangrove conservation area of Tarakan city from December 2010 to May 2011 include preparation, implementation research (data collection, processing and data analysis and report). Result shows that the length of the shell effect on the chitosan content in telescope snail shell and contribution of length shells based on the overall test as much 385,1856 grams of shell powder produced 33,0863 grams chitosan. Keywords : Shell length, Chitosan content, Mangrove conservation of Tarakan city.